Cross-sectional and longitudinal study of the impact of posterior meniscus horn lesions on adjacent cartilage composition, patient-reported outcomes and gait biomechanics in subjects without radiographic osteoarthritis. Issue 5 (May 2017) - Russell, C.; Pedoia, V.; Souza, R.B.; Majumdar, S.
Summary: Objective: The aim of this study was to assess cross-sectional and longitudinal effects of meniscal lesions on adjacent cartilage T 1ρ and T 2 relaxation times, patient-reported outcomes and gait biomechanics. Design: Thirty patients with no cartilage morphological defects reported by Whole Organ MRI Score (WORMS) magnetic resonance imaging (MRI) grading and no radiographic osteoarthritis (OA) (Kellgren–-Lawrence (KL) ≤ 1) were selected, 15 with posterior meniscus horn lesions and 15 matched controls without meniscal lesions. All were imaged on a 3T MR scanner for three consecutive years, except those who dropped from the study. Sagittal and frontal plane kinematic gait data were acquired at baseline. The Knee Injury and Osteoarthritis Outcome Score (KOOS) survey was taken each time. All images were automatically segmented and registered to an atlas for voxel-by-voxel cross-sectional and longitudinal analyses. Results: Relaxation time comparisons between groups showed elevated T 1ρ of the lateral tibia (LP) and elevated T 2 of the medial tibia (MT) and LT at 1 and 2 years in the lesion group. Longitudinal comparisons within each group revealed greater relaxation time elevations over one and 2 years in the group with lesions. KOOS Quality of Life (QOL) was significantly different between the groups at all time points ( P  < 0.05), as were other KOOS subcategories. No significant differences in the frontal or sagittal biomechanics were observed between the groups at baseline. Conclusions: Individuals with healthy cartilage and posterior meniscal horn lesions have increased relaxation times when compared to matched controls, increased relaxation time changes over 2 years, and consistently report a lower KOOS QOL, yet show no difference in gait biomechanics.